ANALISIS PARTISIPASI KERJA RUMAH TANGGA PERTANIAN PEDESAAN JAWA TENGAH - Sri Marwanti (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2006)
Labor Force Participation (LFPR) of rural inhibitant show tend to oncrease and part of them still absorbed in agriculture sector that both increase in quality and in proportion. Using basic dara SUSENAS, this article study about LFPR of household of agriculture in rural of Central Java. Analysis result household of agriculture show that LFPR of household on agriculture decrease with more increase in amount of household member, amount of still attend school, and total income of household